The photocatalytic properties of nanocrystalline materials in different forms. Issue 2 (21st August 2020) - Su, Mingyang
Abstract : Nanocrystalline materials have strong light absorption ability and photocatalysis performance. Different forms of nanocrystalline materials have different photocatalysis performance levels. Therefore, in this paper the photocatalytic properties of nanocrystalline materials in different forms are studied by experiments. In the experiment, the same materials were used, and three different kinds of samples – block, tube and particle – were made according to different manufacturing processes and processing methods. The results show that the bulk and coarse nanocrystalline materials have the largest specific surface area, the largest value of light absorption efficiency and the strongest photocatalytic ability. The specific surface area of the tubular nanocrystalline materials is moderate, the value of light absorption rate is moderate and the photocatalytic capacity is general. The nanocrystalline materials with particle morphology have the smallest specific surface area, the smallest value of light absorption rate and the weakest photocatalytic ability.